EFEKTIFITAS PENGGUNAAN MEDIA POSTER UNTUK MENGENALKAN PAKAIAN DAERAH BAGI ANAK TUNAGRAHITA RINGAN DI SLB AL HIDAYAH PADANG - Rita Kurnia Putri; Markis Yunus; Fatmawati Fatmawati (Jurnal Penelitian Pendidikan Khusus, 2013)
This study originated from the problems that I have found in social studies in the classroom D III / C SLB Al Hidayah Padang on regional clothing. Children's  are not familiar with the regional clothing. This is because in the absence of the use of learning media that can attract the attention of children in learning. During lesson’s procces just using textbooks and worksheets alone. So that children are less interested in learning and tends to feel less excited even bored. For that we need the media to overcome boredom child. This study aims to introduce clothing Sumatra (West Sumatra, North Sumatra, South Sumatra, Aceh, Jambi) using media in teaching social studies poster child for mild mental retardation D grade III / C SLB Al Hidayah Padang. This research approach desainpre Quasi Experiments with test and post-test group design. The subjects were all children of class III D / C in SLB Al Hidayah Padang, amounting to four people. Collecting research data about isisan receipts test and choice as much as 10 questions and the data obtained were analyzed using the Mann Whitney U test.These results indicate that, Uhit = 1 and at the 95% significance level or alpha = 0.05 obtained Utab = 0 to n = 4. Based on the results of the testing criteria Uhit> Utab, accepted, meaning that Ha is accepted and Ho is rejected, it is proved that the effective use of media is used to introduce the poster area for children clothing mild mental retardation class DIII / C SLB Al Hidayah Padang. Thus the authors suggest to the teacher to select appropriate media and engaging with the learning characteristics of children in the media one poster.